Barriers to applying for medical rehabilitation: a time-to-event analysis of employees with severe back pain in Germany - Julia-Marie Zimmer; David Fauser; André Golla; Andreas Wienke; Nadine Schmitt; Matthias Bethge; Wilfried Mau (Medical Journals Sweden, 2022)
Objective: Longitudinal studies on barriers to applying for rehabilitation in Germany are lacking in light of the suspected underutilization of rehabilitation services. The aim of this study was to examine application behaviour in persons with disabling back pain and to identify relevant predictors for making an application. Design: A prospective cohort study with randomized sampling of insurants in the German Pension Insurance, using a questionnaire at baseline and follow-up with linked administrative data for 1.5 years. Subjects/patients: Employed persons (age range 45-59 years) with a high degree of limitations due to back pain and a self-reported risk of permanent work disability (not applied for disability pension, no medical rehabilitation within the last 4 years). Methods: Multivariable Cox regression was used to examine the influence of pre-selected variables on making an application in the follow-up period. Results: Of 690 persons, only 12% applied for rehabilitation. Predictors for making an application were: support from physicians (hazard ratio (HR)=2.24; 95% confidence interval (95% CI) 1.32-3.80), family, and friends (HR=1.67; 95% CI 1.02-2.73), more pain-related disability days (HR=1.02; 95% CI 1.01-1.03), and worse work ability (HR=0.86; 95% CI 0.75-0.97). An intention to apply at baseline mediated the effect of family and physician support on the application. Conclusion: The low number of applications for rehabilitation despite disabling back pain indicates access barriers to, and underuse of, medical rehabilitation.